2011
DOI: 10.1017/s0016672310000625
|View full text |Cite
|
Sign up to set email alerts
|

Thecopiaretrotransposon and horizontal transfer inDrosophila willistoni

Abstract: SummaryThe copia element is a retrotransposon that is hypothesized to have been horizontally transferred from Drosophila melanogaster to some populations of Drosophila willistoni in Florida. Here we have used PCR and Southern blots to screen for sequences similar to copia element in South American populations of D. willistoni, as well as in strains previously shown to be carriers of the element. We have not found the canonical copia element in any of these populations. Unlike the P element, which invaded the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Indeed, the sequenced strain of D. willistoni , Gd-H4-1, corresponds to a population from Guadeloupe Island (Caribbean) [7] that has not been tested in the work of [24]. A similar observation has been made in South American populations of D. willistoni in which no evidence of the HT of Copia was detected [27]. …”
Section: Resultsmentioning
confidence: 78%
“…Indeed, the sequenced strain of D. willistoni , Gd-H4-1, corresponds to a population from Guadeloupe Island (Caribbean) [7] that has not been tested in the work of [24]. A similar observation has been made in South American populations of D. willistoni in which no evidence of the HT of Copia was detected [27]. …”
Section: Resultsmentioning
confidence: 78%
“…A related question is whether the horizontal exchange between D. melanogaster and species of the willistoni group is unidirectional or if species of the willistoni group also recently received TEs from D. melanogaster . It was for example suggested that Copia was recently horizontally transferred from D. melanogaster to D. willistoni , although recent works did not confirm this [Jordan et al, 1999, Rubin et al, 2011].…”
Section: Discussionmentioning
confidence: 99%